Geographical marginality and social aspects of sustainability - Pelc, Stanko (Journal for Geography, 2011)
Geographical marginality as a topic of systematic geographical study occurs in the last two decades since the International Geographical Union (IGU) formed first a Study group and then a Commission to cover this field of geographic research. There is no unique definition of a geographical marginality. In this paper we will briefly present our view of it, to establish a platform for the discussion on the role and importance of sustainability in research of geographically marginal areas. Sustainability will be taken into account in its broadest sense, not only in narrow economic. The main problem of geographically marginal areas and main source of their disadvantages is their insignificance that is in large part a consequence of their location far from centre. When dealing with marginality of an area or region the measures to ensure sustainable economic and social development is often in focus of researchers and developers attention. By some relevant examples from the literature we illustrate our views on how to ensure sustainability and what sustainability actually is.
Keywords: geographical marginality; sustainability